Correlation between pseudotyped virus and authentic virus neutralisation assays, a systematic review and meta-analysis of the literature - Cantoni, Diego; Wilkie, Craig; Bentley, Emma M.; Mayora-Neto, Martin; Wright, Edward; Scott, Simon; Ray, Surajit; Castillo-Olivares, Javier; Heeney, Jonathan Luke; Mattiuzzo, Giada; Temperton, Nigel James (Frontiers in Immunology, 2023)
The virus neutralization assay is a principal method to assess the efficacy of antibodies in blocking viral entry. Due to biosafety handling requirements of viruses classified as hazard group 3 or 4, pseudotyped viruses can be used as safer alternative. However, it is often queried how well the results derived from pseudotyped viruses correlate with authentic virus. This systematic review and meta-analysis was designed to comprehensively evaluate the correlation between the two assays.Methods: Using PubMed and Google Scholar, reports that incorporated neutralisation assays with both pseudotyped virus, authentic virus, and the application of a mathematical formula to assess the relationship between the results, were selected for review. Our searches identified 67 reports, of which 22 underwent a three-level meta-analysis.The three-level meta-analysis revealed a high level of correlation between pseudotyped viruses and authentic viruses when used in an neutralisation assay. Reports that were not included in the meta-analysis also showed a high degree of correlation, with the exception of lentiviral-based pseudotyped Ebola viruses.Pseudotyped viruses identified in this report can be used as a surrogate for authentic virus, though care must be taken in considering which pseudotype core to use when generating new uncharacterised pseudotyped viruses.No. of Reports Correlation Range (Linear R 2 ) Correlation Range (Pearson's) Correlation Range (Spearman's) Correlation Range (Intra-Class)